Sawdust Collector/Spacious Season - Adler, Barbara (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
In this piece, Barbara Adler reflects on the Vancouver arts collective known as Sawdust Collector, which ceased operations during the pandemic. She asks how we might move beyond exhaustion by allowing ourselves the time to slow down and the space to reimagine creative praxes, and by contributing our energies to the unfinished work of others.